David Lagmanovich, Estructura del cuento hispanoamericano. Universidad Veracruzana, Xalapa, 1989; 124 pp. - Zavala, Lauro (El Colegio de México, 1991)
Se reseñó el libro: Estructura del cuento hispanoamericano.